Computational vision and medical image processing : Vipimage 2011 : proceedings of VIPIMAGE 2011, Third ECCOMAS Thematic Conference on Computational Vision and Medical Image Processing, Olhão, Algarve, Portugal, 12-14 October 2011 /: Vipimage 2011 : proceedings of VIPIMAGE 2011, Third ECCOMAS Thematic Conference on Computational Vision and Medical Image Processing, Olhão, Algarve, Portugal, 12-14 October 2011. (©2012) - Unknown
No abstract available